PENGUATAN KARAKTER BELA NEGARA GENERASI MUDA MELALUI WORKSHOP FILM PENDEK - Fajar Edyana; Firdaus Noor; Nuril Ashivah Misbah (Abdi Seni, 2024)
Exactly how nationalism can have a strong influence in films and reflect or reveal a national "essence" in increasing knowledge, skills, andopportunities for the younger generation to collaborate in the production of short films that highlight the values of defending the country are the goals to be achieved in this community service program (PKM). Through the mentoring method in the form of collaborative practice, partners as young people from a theater arts background are given knowledge and skills through three stages, namely the planning, implementation, and reflection stages, to translate national identity in short films. The results were that the short film production workshop was considered successful in driving the creativity of actors' sk Karakter, Nasionalisme, Teater, Film Pendek ills in the art of acting into the medium of film and being an evaluative moment to raise awareness of strengthening the character of National Defense through the medium of short films.